Implementasi Metode Analytical Hierarchy Process (AHP) Untuk Evaluasi dan Pemilihan Karyawan Terbaik Berdasarkan Kinerja dan Kompetensi Studi Kasus Burger KiNG Cipondoh Raya - Endar Nirmala; Anggi Pradana Yoani (Teknik Informatika Universitas Pamulang, 2026)
Human resources are a crucial asset in supporting organizational success, particularly in the fast-food restaurant industry, which demands optimal employee performance and competence. However, employee evaluation processes that are still conducted manually tend to cause subjectivity and inconsistency in decision-making. This study aims to design and implement a decision support system to evaluate and determine the best employee at Burger King Cipondoh Raya using the Analytical Hierarchy Process (AHP) method. The AHP method was selected because it is capable of decomposing complex problems into a hierarchical structure and producing objective priority weights through pairwise comparisons. The evaluation criteria consist of two main aspects, namely performance, which includes responsibility, productivity, and work discipline, and competence, which covers knowledge, skills, and work attitude. The system was developed as a web-based application using the PHP programming language and MySQL as the database, following the waterfall development model. The data processing results indicate that the system is able to generate an objective employee ranking, in which the employee with the highest preference value obtained a final score of 0.449, and was therefore determined as the best employee. These results demonstrate that the implementation of the AHP method can assist management in conducting employee evaluations in a more accurate, fair, and measurable manner, as well as supporting accountable managerial decision-making.